Film criticism in the digital age - Frey, Mattias; Sayad, Cecilia (Rutgers University Press, 2015)
"Over the past decade, as digital media has expanded and print outlets have declined, pundits have bemoaned a "crisis of criticism" and mourned the "death of the critic." Now that well-paying jobs in film criticism have largely evaporated, while blogs, message boards, and social media have given new meaning to the saying that "everyone's a critic," urgent questions have emerged about the status and purpose of film criticism in the twenty-first century. In Film Criticism in the Digital Age, ten scholars from across the globe come together to consider whether we are witnessing the extinction of serious film criticism or seeing the start of its rebirth in a new form. Drawing from a wide variety of case studies and methodological perspectives, the book's contributors find many signs of the film critic's declining clout, but they also locate surprising examples of how critics--whether moonlighting bloggers or salaried writers--have been able to intervene in current popular discourse about arts and culture. In addition to collecting a plethora of scholarly perspectives, Film Criticism in the Digital Age includes statements from key bloggers and print critics, like Armond White and Nick James. Neither an uncritical celebration of digital culture nor a jeremiad against it, this anthology offers a comprehensive look at the challenges and possibilities that the Internet brings to the evaluation, promotion, and explanation of artistic works."--Publisher's description